Flash-and-Freeze: Coordinating Optogenetic Stimulation with Rapid Freezing to Visualize Membrane Dynamics at Synapses with Millisecond Resolution - Watanabe, Shigeki (Frontiers in Synaptic Neuroscience, 2016)
Electron microscopy depicts subcellular structures at synapses exquisitely but only captures static images. To visualize membrane dynamics, we have developed a novel technique, called flash-and-freeze, which induces neuronal activity with a flash of light and captures the membrane dynamics by rapid freezing. For characterizing membrane movements during synaptic transmission, a light-sensitive cation channel, channelrhodopsin, is heterologously expressed in mouse hippocampal neurons or in Caenorhabditis elegans motor neurons. A brief pulse of blue light activates channelrhodopsin and induces an action potential, leading to synaptic transmission. Following the light stimulation, neurons are frozen at different time intervals ranging from 10 ms to 20 s. Electron micrographs are then acquired from each time point to visualize the morphological changes. Using this approach, we have characterized a novel form of endocytosis, ultrafast endocytosis, which rapidly removes excess membrane added to the surface during neurotransmission. The flash-and-freeze approach can be adapted to study other cellular phenomena that can be induced by light-sensitive genetic or pharmacological tools.